Severe sepsis due to severe falciparum malaria and leptospirosis co-infection treated with activated protein C - Gupta Dheeraj; Agarwal Ritesh; Srinivas Rajagopala (Malaria Journal, 2007)
Abstract Co-infection with falciparum malaria and leptospirosis is uncommon. The aim of this study is to report a case of severe sepsis secondary to dual infection with falciparum malaria and leptospirosis. The literature is also reviewed on the clinical course of such co-infections, and the possible mechanisms and treatment of patients with life-threatening malaria and leptospirosis with activated protein C. The patient was a 25-year old male admitted in the Respiratory Intensive Care Unit (RICU) with fever, haemolysis, acute renal failure, hepatitis, acute lung injury (ALI) and altered sensorium. A syndromic evaluation was done and investigations revealed falciparum parasitaemia. He was treated with parenteral artesunate, ceftriaxone and doxycycline, and adjunctive therapies as for severe sepsis. Infusion of activated protein C was started 20 hours after onset of organ dysfunction, and intensive haemodialysis was instituted. Over the next four days the patient became afebrile with progressive resolution of ALI, renal failure and hepatitis. His Leptospira serology (requested as part of the evaluation) was reported positive on day 5. Dual infections are common and under-recognized in the tropics. Failure to treat potential co-infections may lead to poor outcomes. Acute lung injury in falciparum malaria has high mortality rates and therapy as for severe sepsis may improve survival. Adjunctive therapies, including activated protein C, cannot replace source eradication.